A complex flow phantom for medical imaging: ring vortex phantom design and technical specification. (3rd April 2019) - Ambrogio, Simone; Walker, Adrian; Narracott, Andrew; Ferrari, Simone; Verma, Prashant; Fenner, John
Abstract: Cardiovascular fluid dynamics exhibit complex flow patterns, such as recirculation and vortices. Quantitative analysis of these complexities supports diagnosis, leading to early prediction of pathologies. Quality assurance of technologies that image such flows is challenging but essential, and to this end, a novel, cost-effective, portable, complex flow phantom is proposed and the design specifications are provided. The vortex ring is the flow of choice because it offers patterns comparable to physiological flows and is stable, predictable, reproducible and controllable. This design employs a piston/cylinder system for vortex ring generation, coupled to an imaging tank full of fluid, for vortex propagation. The phantom is motor-driven and by varying piston speed, piston displacement and orifice size, vortex rings with different characteristics can be produced. Two measurement methods, namely Laser-PIV and an optical/video technique, were used to test the phantom under a combination of configurations. Vortex rings with a range of travelling velocities (approximately 1–80 cm/s) and different output-orifice diameters (10–25 mm) were produced with reproducibility typically better than ±10%. Although ultrasound compatibility has been demonstrated, longer-term ambitions include adapting the design to support comparative studies with different modalities, such as MRA and X-ray-CTA.